Improving the quality and use of immunization and surveillance data: Summary report of the Working Group of the Strategic Advisory Group of Experts on Immunization. Issue 46 (27th October 2020) - Scobie, Heather M.; Edelstein, Michael; Nicol, Edward; Morice, Ana; Rahimi, Nargis; MacDonald, Noni E.; Carolina Danovaro-Holliday, M.; Jawad, Jaleela; ,
Highlights: Reported to SAGE on immunization and surveillance data quality & use, October 2019. Improvements since 2011, but gaps persist in data quality (fit-for-purpose) and use. Improving data quality and use requires better governance, people, tools, and processes. Better use of existing data needed to continuously improve programme performance. Report relevant for "data-guided" implementation of the Immunization Agenda 2030. Abstract: Concerns about the quality and use of immunization and vaccine-preventable disease (VPD) surveillance data have been highlighted on the global agenda for over two decades. In August 2017, the Strategic Advisory Group of Experts (SAGE) established a Working Group (WG) on the Quality and Use of Global Immunization and Surveillance Data to review the current status and evidence to make recommendations, which were presented to SAGE in October 2019. The WG synthesized evidence from landscape analyses, literature reviews, country case-studies, a data triangulation analysis, as well as surveys of experts. Data quality (DQ) was defined as data that are accurate, precise, relevant, complete, and timely enough for the intended purpose (fit-for-purpose), and data use as the degree to which data are actually used for defined purposes, e.g., immunization programme management, performance monitoring, decision-making. The WG outlined roles and responsibilities for immunization and surveillance DQ and use by programme level. The WG found that while DQ is dependent on quality data collection at health facilities, many interventions have targeted national and subnational levels, or have focused on new technologies, rather than the people and enabling environments required for functional information systems. The WG concluded that sustainable improvements in immunization and surveillance DQ and use will require efforts across the health system — governance, people, tools, and processes, including use of data for continuous quality improvement (CQI) — and that the approaches need to be context-specific, country-owned and driven from the frontline up. At the country level, major efforts are needed to: (1) embed monitoring DQ and use alongside monitoring of immunization and surveillance performance, (2) increase workforce capacity and capability for DQ and use, starting at the facility level, (3) improve the accuracy of immunization programme targets (denominators), (4) enhance use of existing data for tailored programme action (e.g., immunization programme planning, management and policy-change), (5) adopt a data-driven CQI approach as part of health system strengthening, (6) strengthen governance around piloting and implementation of new information and communication technology tools, and (7) improve data sharing and knowledge management across areas and organizations for improved transparency and efficiency. Global and regional partners are requested to support countries in adopting relevant recommendations for their setting and to continue strengthening the reporting and monitoring of immunization and VPD surveillance data through processes periodic needs assessment and revision processes. This summary of the WG's findings and recommendations can support "data-guided" implementation of the new Immunization Agenda 2030.